Hepatocellular carcinoma cells induce γδ T cells through metabolic reprogramming into tumor-progressive subpopulation - Xia, Jinkun; Wang, Chaoyu; Li, Biao (Frontiers in Oncology, 2024)
Tumor immune microenvironment (TIME) is a tiny structure that contains multiple immune cell components around tumor cells, which plays an important role in tumorigenesis, and is also the potential core area of activated immunotherapy. How immune cells with tumor-killing capacity in TIME are hijacked by tumor cells during the progression of tumorigenesis and transformed into subpopulations that facilitate cancer advancement is a question that needs to be urgently addressed nowadays. γδ T cells (their T cell receptors are composed of γ and δ chains), a unique T cell subpopulation distinguished from conventional αβ T cells, are involved in a variety of immune response processes through direct tumor-killing effects and/or indirectly influencing the activity of other immune cells. However, the presence of γδ T cells in the tumor microenvironment (TME) has been reported to be associated with poor prognosis in some tumors, suggesting that certain γδ T cell subsets may also have pro-tumorigenic effects. Recent studies have revealed that metabolic pathways such as activation of glycolysis, increase of lipid metabolism, enhancement of mitochondrial biosynthesis, alterations of fatty acid metabolism reshape the local TME, and immune cells trigger metabolic adaptation through metabolic reprogramming to meet their own needs and play the role of anti-tumor or immunosuppression. Combining previous studies and our bioinformatics results, we hypothesize that γδT cells compete for resources with hepatocellular carcinoma (HCC) cells by means of fatty acid metabolic regulation in the TME, which results in the weakening or loss of their ability to recognize and kill HCC cells through genetic and epigenetic alterations, thus allowing γδT cells to be hijacked by HCC cells as a subpopulation that promotes HCC progression.